Influence of Rock Mass Properties on Performance of Hard Rock TBMs - Ahmad Ramezanzadeh; Jamal Rostami; Richard Kastner (Society for Mining, Metallurgy & Exploration, 2005)
Improving the accuracy of the performance prediction models for hard rock Tunnel Boring Machines (TBMs) is important in estimation of the schedule and cost of tunnelling in related projects. The effects of rock mass on performance of TBMs has been studied extensively, yet due to the complex nature of the process, impact of many parameters influencing machine advance rate are not very clear and there is still room for improvements. More accurate estimates can be obtained by better understanding of operating parameters in various geological conditions and can lead to matching machine specifications with job conditions, optimizing machine performance, and avoiding long delays and downtime for increased productivity. This paper will offer review of two case histories including Queens Water tunnel in New York and KCRC project in Hong Kong. The analysis of the available field data, including the geological back mapping and results of laboratory testing of rock mechanical properties, machine operational parameters and achieved rate of penetration will be presented. This includes statistical analysis of available field data to provide a better understanding of the influence of rock mass properties on performance of hard rock TBMs as well as related formulas to improve performance estimates.